Oxidized maize starch: characterization and its effect on the biodegradable films i. Characterization of maize starch oxidized by sodium hypochlorite - Phi Hung, Dao; Nam, Truong Thi; Phuc, Mac Van; Hiep, Nguyen Anh; Thanh, Trinh Van; Vuong, Nguyen THien (Vietnam Journal of Science and Technology, 2016)
The effects of hypochlorite level, i.e. 0.5; 1 and 2 active chlorine g/100g starch, on the structures and physicochemical properties of oxidized maize starch were investigated. The obtained results shown that oxidation degree grew up with increasing hypochlorite concentration, specially, the carboxyl content saw higher increased than the content of carbonyl. SEM images indicated that surface of oxidized maize starches were rougher than native starch. The surface of oxidized starches saw rougher with increasing hypochlorite level. However, the DSC results illustrated that there was no significant difference of gelatinization temperature between the native starch and oxidized starches.